Incorporating evidence based approaches in the management of emerging public health challenges 13th National Public Health Colloquium, 25-26th July 2006, The Crown Princess Hotel, City Square, Kuala Lumpur - National Public Health Colloquium 2006 : Kuala Lumpur); Universiti Kebangsaan Malaysia. Fakulti Perubatan. Jabatan Kesihatan Masyarakat; Persatuan Pakar Perubatan Kesihatan Awam Malaysia (Kuala Lumpur : Department of Community Health, Faculty of Medicine, UKM, 2006)
Contained paper work for conference and symposium papers
Keywords: Public health -- Congresses; Medical care -- Developing countries -- Congresses; Health policy; Health services administration